Effects of Ocean Acidification on Calcification of the Sub-Antarctic Pteropod Limacina retroversa - Mekkes, Lisette; Sepúlveda-Rodríguez, Guadalupe; Bielkinaitė, Gintarė; Wall-Palmer, Deborah; Brummer, Geert-Jan A.; Dämmer, Linda K.; Huisman, Jef; van Loon, Emiel; Renema, Willem; Peijnenburg, Katja T. C. A. (Frontiers in Marine Science, 2021)
Ocean acidification is expected to impact the high latitude oceans first, as CO2 dissolves more easily in colder waters. At the current rate of anthropogenic CO2 emissions, the sub-Antarctic Zone will start to experience undersaturated conditions with respect to aragonite within the next few decades, which will affect marine calcifying organisms. Shelled pteropods, a group of calcifying zooplankton, are considered to be especially sensitive to changes in carbonate chemistry because of their thin aragonite shells. Limacina retroversa is the most abundant pteropod in sub-Antarctic waters, and plays an important role in the carbonate pump. However, not much is known about its response to ocean acidification. In this study, we investigated differences in calcification between L. retroversa individuals exposed to ocean carbonate chemistry conditions of the past (pH 8.19; mid-1880s), present (pH 8.06), and near-future (pH 7.93; predicted for 2050) in the sub-Antarctic. After 3 days of exposure, calcification responses were quantified by calcein staining, shell weighing, and Micro-CT scanning. In pteropods exposed to past conditions, calcification occurred over the entire shell and the leading edge of the last whorl, whilst individuals incubated under present and near-future conditions mostly invested in extending their shells, rather than calcifying over their entire shell. Moreover, individuals exposed to past conditions formed larger shell volumes compared to present and future conditions, suggesting that calcification is already decreased in today’s sub-Antarctic waters. Shells of individuals incubated under near-future conditions did not increase in shell weight during the incubation, and had a lower density compared to past and present conditions, suggesting that calcification will be further compromised in the future. This demonstrates the high sensitivity of L. retroversa to relatively small and short-term changes in carbonate chemistry. A reduction in calcification of L. retroversa in the rapidly acidifying waters of the sub-Antarctic will have a major impact on aragonite-CaCO3 export from oceanic surface waters to the deep sea.